Aikido, un arte marcial (acceso a otro modo de ser) - Nalda Albiac, José Santos (Revista de Artes Marciales Asiáticas, 2012)
<span style="mso-ascii-font-family: Calibri; mso-fareast-font-family: Calibri; mso-hansi-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: PT-BR; mso-bidi-font-weight: bold;" lang="PT-BR">André Protin. Barcelona: Ibis, 1998 (3ª ed.). 326 páginas. 21,50x15 cm. I.S.B.N.: 84-86512-34-4.